CAM FITTING UNIT OF DEVICEFOR UNSCREWING CATCHED PIPES IN THE WELL - Gavryliv, S. Yu.; Lyakh, M. M.; Gavryliv, Yu. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
Improving the efficiency of repair work in elimination of drilling pipe accidents in the well is an urgent task of oil companies and is achieved through usage of special devices and tools. Authors patented and manufactured a device for unscrewing pipes in casing with a nominal diameter of D = 114 mm. Cycle of the device for unscrewing pipes in the well consists of three periods: freewheeling, jamming of the carrier of the device for unscrewing the trapped pipes and the period of wedging. The article analyses the operating conditions of the device locking unit during the first two periods. Formulas for determining the force of pressing the cams to the casing during freewheel, as well as the moment of friction forces and friction power for this case are proposed. We obtain the dependence of the maximum allowable initial angle of jamming on the coefficient of friction and geometric parameters of the device. It is planned to test the device for unscrewing pipes in industrial conditions of LLC "Factorial" (Poltava).